PERAN KNOWLEDGE MANAGEMENT SEBAGAI PENGUNGKIT KEBERHASILAN ORGANISASI - Hadi, A Sigit Pramono; Ailani, Aretha Widi (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
Knowledge management is a procedure that assists companies in executing the processes of sorting, identification, arrangement, dissemination, and transfer of information as well as fundamental skills that constitute the competency of the company. The objective of knowledge management is to provide an understanding to all individuals regarding the managerial system. The primary resource that needs to be professionally managed is human resources, aiming to establish a more effective and efficient organizational management system. In an organization or business, each employee can experience the benefits of implementing knowledge management without having to start from scratch. Conversely, they can swiftly acquire such knowledge and enhance their individual competencies as part of leadership values development that will ultimately lead to organizational development. This article constitutes a library study and identifies that knowledge management plays a crucial role in enhancing organizational leadership capacity.